The impact of increased life expectancy on the level pension - Alleiddine Ayed Zambaa (Atlantic Review of Economics, 2015)
This paper proposes an overlapping generation model along the lines of the papers by Fanti and Gori (2008). Its objective is to study the effect of demographic shocks on the level pension respectively in the PAYG and funded system within the context of increased life expectancy at long-run.
Keywords: H55; J13; 330; life expectancy; pension system; overlapping generation model